Effect of Levothyroxine Replacement on Lipid Profile and Renal Function of Primary and Subclinical Hypothyroid Patients (BIRDEM Medical Journal, 2017)
Background: Hypothyroidism is an important endocrine disorder associated with deleterious effects on multiple systems including cardiovascular, musculoskeletal, renal and nervous system. It is established that thyroxine replacement shows improvement in many clinical and biochemical parameters of overt hypothyroidism, but there is scarce data about these disorders in this sub-continent. The present study intends to find out the effect of thyroxine replacement on lipid profile and renal function in hypothyroid patients.Methods: This was an observational cohort study, done in endocrine inpatient and outpatient departments of BIRDEM General Hospital from August 2013 to July 2014. Patients with newly detected hypothyroidism, both primary and subclinical, were selected by convenient sampling. A semi-structured questionnaire was used to collect the clinical and laboratory informations from the patients. Baseline clinical and laboratory informations including lipid profile and serum creatinine were collected and e-GFR was calculated. Then tablet levothyroxine was started at a dose of 25 micrograms/day and adjusted by 12.5-25 micrograms/day dose increments 4-6 weekly till FT4 and TSH were normalized. After 6 months, clinical and biochemical data were collected and e-GFR calculated.Results: Seventy four hypothyroid patients were followed up for 6 months. All the patients became euthyroid during this time with thyroxine replacement (mean daily dose of thyroxine 96.61 ±25.62 micrograms). There was significant improvement in hypothyroid symptoms and significant reduction in weight and systolic and diastolic blood pressure in the patients after thyroxine replacement. There was reduction in total cholesterol (187.66 ±19.90 mg/dl to 164.37±17.49 mg/dl, P